Rowing performance of female and male rowers - Yoshiga, C. C.; Higuchi, M. (Scandinavian Journal of Medicine & Science in Sports, 2003)
This study evaluated the rowing performance of female and male rowers with regard to their body size. Body height, body mass, fat-free mass, maximal oxygen uptake (VO2max), and "2000-m" rowing ergometer performance were measured in 71 females (age range 18-24 years, height 153-173 cm, body mass 43-69 kg, fat-free mass 34-55 kg; VO2max 2.1-3.9 L min1; 2000-m time 437-556 s) and 120 males (age 18-24 years, height 164-193 cm, body mass 58-95 kg, fat-free mass 50-81 kg; VO2max 3.4-5.6 L min1; 2000-m time 378-484 s). Rowing performance was correlated to body height (r=0.81, P<0.001), body mass (r=0.85, P<0.001), fat-free mass (r=0.91, P<0.001), and VO2max (r=0.90, P<0.001). However, rowing time was slower in the females than in the males with a similar body height (by 10%) and body mass (by 9%), but the sex difference was smaller when the fat-free mass (by 4%) and VO2max (by 4%) were matched. This study suggests that individuals with large body size and aerobic capacity possess an advantage for a 2000-m row on an ergometer. However, among females and males the variation in body size and aerobic capacity cannot explain the entire sex difference in ergometer rowing performance.